Egg Production Performance of the Local Kabyle Hen and its Crossbreeds with ISA-Brown Strain in Semi-Intensive Conditions - Moula , Nassim; Diaw, Mamadou Tandiang; Salhi, Abdellah; Farnir, Frederic; Antoine-Moussiaux, Nicolas; Leroy, Pascal (International Journal of Poultry Science, 2013)
A cross between the ISA-Brown industrial strain and an Algerian local (Kabyle) breed was compared with the Algerian local (Kabyle) hen. The comparison during the egg production period was done in individual cages, in a ventilated henhouse without any particular isolation. The same commercial diet has been provided over three time periods (35 to 36 weeks, 50 to 51 weeks and 65 to 66 weeks of age). Egg number and body weight at first egg was significantly lower in the Kabyle local breed. Mortality was almost equal during the breeding period and the egg production periods for the two genotypes. The Kabyle hen eggs, in spite of a weight which was lower (43.70 to 53.37 g according to the age), gave yolk to albumen ratio similar to the ISAKAB cross (0.52 to 0.58 according to age). Finally, the ISAKAB cross was better in terms of egg production and egg quality than the local hen, in test conditions.